2018
DOI: 10.1002/app.46429
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different compatibilizers on the morphology and properties of PA6/PET/glass fiber composites

Abstract: Three kinds of compatibilizers, ethylene-ethyl acrylate copolymer (EEA), ethylene-ethyl acrylate-glycidyl methacrylate copolymer (EAG), and ethene-maleic anhydride-glycidyl methacrylate copolymer (EMG), were introduced to PA6/PET/GF blends for the first time to study the effect of different compatibilizers on composite. EEA, EAG, and EMG showed different effect on the properties of PA6/PET/GF blends. An observation of the GF-resin interface by scanning electronic microscope indicated EAG and EMG enhanced the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Li et al [103] studied the influence of three different compatibilizers on the morphology and mechanical properties of PA6/polyethylene terephthalate (PET)/GF (49/ 21/30 weight ratio). The three different compatibilizers used in this study were ethylene-ethyl acrylate copolymer, ethylene-ethyl acrylate-glycidyl methacrylate copolymer (EAG), and ethene-maleic anhydride-glycidyl methacrylate copolymer (EMG) (1 wt%).…”
Section: Pa6 Blend-based Microfiller or Fiber Reinforced Hybrid Commentioning
confidence: 99%
“…Li et al [103] studied the influence of three different compatibilizers on the morphology and mechanical properties of PA6/polyethylene terephthalate (PET)/GF (49/ 21/30 weight ratio). The three different compatibilizers used in this study were ethylene-ethyl acrylate copolymer, ethylene-ethyl acrylate-glycidyl methacrylate copolymer (EAG), and ethene-maleic anhydride-glycidyl methacrylate copolymer (EMG) (1 wt%).…”
Section: Pa6 Blend-based Microfiller or Fiber Reinforced Hybrid Commentioning
confidence: 99%
“…PP, a thermoplastic polymer, is known by its outstanding cost‐to‐performance ratio and has motivated researchers to enhance its properties further, for example, through reinforcement with various particulates, fibers, and inorganic fillers . The effectiveness of inorganic fillers in improving the physical and mechanical properties of polymers strongly depends on various factors such as filler aspect ratio, size, shape, surface characteristics, interfacial adhesion, and degree of filler dispersion . It has been reported that inorganic filler such as rattan powder, glass fiber, etc.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Recently, there has been observed an increase in the number of studies published on the technology of polymer compatibilization. [1,[7][8][9][10] There are many compatibilizations strategies, either non-reactive or reactive ones. In a nonreactive compatibilization, the addition of a copolymer can be an excellent alternative to improve mechanical properties, because it can interact with both phases, reducing the interphase tension.…”
Section: Doi: 101002/masy202000032mentioning
confidence: 99%
“…Blends of PA with rubbers have been extensively studied in order to obtain new materials with good impact properties (thermoplastic elastomers). [1][2][3][4][5] An appropriate range of rubber particle size and uniform distribution of rubber particles in PA phases are requirements to reinforce PA/rubber blends.…”
Section: Introductionmentioning
confidence: 99%